From shariah to SDGs: a hybrid review of sustainable sukuk research - Fatwasari Soeratno Putri; Doddy Setiawan (Universitas Islam Negeri Walisongo Semarang, 2026)
Purpose - This study examines the intellectual structure and conceptual pillars of sustainable sukuk research, identifying theoretical, contextual, and methodological gaps and proposing a future research agenda. Method - This study employs an integrated mixed-methods design combining bibliometric analysis with a Theory-Context-Method (TCM)-based Systematic Literature Review of 45 Scopus-indexed articles, analyzed using VOSviewer and RStudio, with article selection following the PRISMA protocol. Result - A bibliometric analysis demonstrates significant growth in publications since 2019, with researchers from Malaysia and Indonesia leading the field. The analysis delineates four primary thematic clusters: green sukuk, Islamic finance, macroeconomic impact, and climate change. TCM indicates that 60% of studies are theoretical, with Maqasid al-Shariah emerging as the predominant focus. Geographic coverage is highly concentrated in Southeast Asia, while qualitative methodologies constitute 66.7% of the research approaches. Social sukuk and sustainability sukuk are largely absent as independent research topics, highlighting a fundamental misalignment between the ICMA-defined market architecture and the prevailing academic discourse. Implication - Future research should examine social sukuk and sustainability sukuk as standalone instruments, extend empirical inquiry to GCC and African markets, and adopt quantitative and mixed-methods designs to advance the field from its current exploratory stage toward explanatory and policy-relevant research. Originality - This is the first study to examine the full ICMA-defined sustainable sukuk spectrum as a unified ecosystem, delivering a comprehensive diagnosis of the field's structural gaps and a forward-looking research agenda.